Hipertrofi Tonsil Bilateral dengan Rinitis Alergi Intermiten Ringan: Laporan Kasus - Vania Christy M. Panjaitan; Mukhlis Imanto (Medula, 2026)
Tonsillar hypertrophy is an enlargement of the tonsillar tissue that may result from recurrent infections, chronic inflammation, or allergic processes. This condition can lead to upper airway obstruction, dysphagia, sleep disturbances, and alterations in voice resonance. Allergic rhinitis is an inflammatory disorder of the nasal mucosa mediated by immunoglobulin E (IgE) following exposure to allergens. We report the case of a 28-year-old woman who presented to the Otorhinolaryngology Clinic of Dr. H. Abdul Moeloek Regional General Hospital with a lifelong complaint of a nasal voice, accompanied by alternating nasal obstruction, clear rhinorrhea, recurrent sneezing, and mild dyspnea during sleep triggered by dust, cat dander, and cold air. Physical examination revealed grade T4-T4 tonsillar hypertrophy without signs of active infection. Anterior rhinoscopy demonstrated serous nasal discharge and a livid nasal septal mucosa, while nasal endoscopy showed patent nasal cavities with positive secretions. Laboratory findings revealed elevated eosinophil count 4,2% (normal : 2%-4%). Based on the patient's history, physical examination, endoscopic findings, and supporting investigations, a diagnosis of bilateral tonsillar hypertrophy without active infection associated with moderate-severe intermittent allergic rhinitis was established. Management consisted of loratadine as a second-generation antihistamine, fluticasone furoate nasal spray as an intranasal corticosteroid, allergen avoidance education, and environmental control measures. Considering the presence of severe tonsillar hypertrophy causing impaired voice resonance and potential upper airway obstruction, tonsillectomy was planned as definitive treatment; however, no follow-up or postoperative evaluation had been performed at the time this report was written. The patient’s prognosis was considered favorable with appropriate therapy and adequate control of triggering factors.